Pemetaan Pajak Daerah dan Retribusi Daerah di Pangkalpinang - Rahmadoni, Firman; Safitri, Marlina; Suparlan, Suparlan; Reniati, Reniati; Rahayu, Rini Luciani; Ridwan, Muhammad Qomaruddin (Jurnal Bina Praja, 2022)
Regional autonomy provides opportunities and challenges for Regional Governments to manage and explore sources of Regional Revenue. As the Capital of the Province, Pangkalpinang still relies on transfers, fund and yet their regional revenue is very low. This study tries to identify and map tax and levy revenues in Pangkalpinang and then formulate strategic recommendations that the Government may consider increasing regional revenue. This study analyzes the effectiveness, contribution, and growth of regional tax and retribution revenue in Pangkalpinang between 2016 and 2020. The contribution and growth analysis results are the basis for the Klassen analysis. This study's results indicate that tax revenue's effectiveness in the Pangkalpinang rate is 114.54%, while the effectiveness of retribution is 96.61%. The regional tax revenue with the largest contribution is street lighting tax, which contributes 36.49%. In contrast, the largest contribution of retribution is the revenue from the use of regional wealth, which is 25.05%. Based on Klassen's analysis, knowing that four sectors are in the developing category, four sectors are in the advanced but depressed category, five sectors are in the potential category, and the remaining nineteen sectors are in the lagging category. Therefore, the researcher suggests that the Government focus on developing and developing depressed sectors if they want to increase local tax and retribution revenues in the short term. However, they must focus on developing potential sectors if they're going to increase regional tax and levy revenues long-term.